SCIENTIFIC AND PRACTICAL THEORY AND CONCEPT OF DIALECTS RESEARCH (Scientific journal of the Fergana State University, 2023)
The article is devoted to the theory and concept of scientific and practical research of Uzbek national dialects. The above actions were carried out diachronically and synchronously with scientific observations to rationally substantiate the theory and concept, as well as its types. They give an idea of the development of "Uzbek dialectology", "Uzbek dialectical lexicography", "Historical dialectology".